The torture is a crime against humanity. Analysis from international instruments (2014)
The so-called “crimes against humanity” are topical, considering an event the fact of establishing a genuine culture of respect for human rights; we can identify the boom that have taken and their relevance in the field of regulation and legal argumentation. This analysis aims to take a global look at the various international instruments that are applicable to the crime of torture. First, this job implicates the “crimes against humanity” concept, analyzing the specific treatment that is applicable to the crime of torture. We take the development and legal management of an element used by international institutions respect the imprescriptibly of the crimes considerate as crimes against humanity. (Parenti,p. 2007).